Optimized Placement of Distributed Fiber Optic Sensors for Accurate Strain Monitoring of Buried Pipelines in Landslide-Prone Areas - Alarifi Hamzh; Hisham Mohamad; Phromphat Thansirichaisree (IEEE Access)
Buried pipelines are vulnerable to damage from geohazards such as landslides, making accurate strain monitoring essential for early hazard detection and integrity management. While conventional strain monitoring tools face limitations in long-distance applications, distributed fibre optic sensing (DFOS) offers continuous strain measurement with high spatial resolution along extended pipeline networks. This study proposes an optimised DFOS placement strategy for early-stage strain detection induced by lateral soil movement. A novel laboratory-scale sandbox model was developed to simulate soil–pipeline interaction, with fibre optic cables installed at varying positions relative to the pipe. Complementary finite element analysis using ABAQUS was conducted to replicate and validate the physical test conditions. Results indicate that placing DFOS cables at a distance of 1.5D to 2D from the pipe (where D is the pipe diameter) provides optimal strain detection. Experimental and numerical results showed strong agreement, with an average strain deviation of less than 11%. The proposed placement approach enhances DFOS performance for buried pipeline monitoring and offers a practical, scalable solution for early-warning applications in geohazard-prone environments.